2004
DOI: 10.7863/jum.2004.23.6.829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lymph Node Perfusion Using Continuous Mode Harmonic Ultrasonography With a Second‐Generation Contrast Agent

Abstract: Superficial lymph nodes can be characterized as being neoplastic or benign with a high degree of diagnostic accuracy on the basis of the perfusion characteristics evaluated by CE-HUS. This technique has been shown to afford a higher degree of accuracy than currently obtainable by any other ultrasonographic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 23 publications
4
77
3
1
Order By: Relevance
“…In lymph node pathologies CEUS shows a high accuracy in distinguishing benign from metastastic lesions as enhancement is intense and homogeneous in more than 90% of benign lesions, whereas enhancement is absent or poor in metastatic lesions [11,12]. Lymphomas present a variable enhancement pattern in the early arterial phase, often showing an overlap with both benign and metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lymph node pathologies CEUS shows a high accuracy in distinguishing benign from metastastic lesions as enhancement is intense and homogeneous in more than 90% of benign lesions, whereas enhancement is absent or poor in metastatic lesions [11,12]. Lymphomas present a variable enhancement pattern in the early arterial phase, often showing an overlap with both benign and metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) examination of the mediastinum is an effective imaging method with an elevated sensitivity compared to traditional radiographic examination in patients with mediastinal masses, and it is only outperformed by CT in the examination of the posterior mediastinum and the paravertebral region [3e5]. Moreover, contrast enhanced US (CEUS) is proving increasingly useful in the differential diagnosis of lymph node masses [12,13], and US-guided mediastinal biopsy is a valid alternative to CT-guided mediastinal biopsy and even more to mediastinal biopsy carried out during mediastinoscopy [6].…”
Section: Introductionmentioning
confidence: 99%
“…3, scheme 4). branches, give ultrasound the use of second-generation ultrasound contrast agents in scans with a low mechanical index offer new possibilities for the assessment of lymph node vascularity, including parenchymal microperfusion as well as large vessel branches [14].…”
Section: Discussionmentioning
confidence: 99%
“…Scant or absent perfusion can be observed in widespread metastatic infiltration, reflecting presence of large areas of necrosis. Based on these features, Rubaltelli et al found a specificity, sensitivity, and accuracy in differentiation between benign and metastatic nodes of 93%, 92%, and 93%, respectively [94]. Furthermore, when signal time-intensity curves are generated and parametric images are calculated the perfusion parameters, such as the arrival time, time to peak, and peak signal intensity, the difference between peak signal intensity in hyper enhancing and hypo enhancing regions are higher in metastatic LN [95].…”
Section: Lymphadenopathymentioning
confidence: 99%